Palladium orthometallated complexes containing acetophenoneoxime: Synthesis, crystal structures and hirshfeld surface analysis - Bozza, Gabriela F. [UNESP] (2019)
The bridge-splitting reaction between [Pd(C2,N-aphox)(μ-Cl)]2 and phosphines (L), in a 1:2 ratio, yielded neutral mononuclear cyclopalladated compounds of the type [PdCl(C2,N-aphox)(L)] {aphox = acetophenoneoxime; L = triphenylphosphine (1), tris(4-fluorophenyl)phosphine (2), tri-cyclohexylphosphine (3), diphenyl(p-toluyl)phosphine (4), tris-(4-methoxyphenyl)phosphine (5) and tri(p-toluyl)phosphine (6)}. The compounds were characterized by elemental analyses, IR and 1H-, 13C{1H}- and 31P{1H}-NMR spectroscopies. The crystal and molecular structures of 1–5 were determined by single-crystal X-ray diffraction. After that, the Hirshfeld surface calculations were carried out to explore the nature and major contributions of different intermolecular contacts towards crystal packing stability.